Precursor B-cell acute lymphoblastic leukemia presenting with isolated skin relapse: a pediatric case report - Yeter Düzenli Kar; Zeynep Canan Özdemir; Ersin Töret; Evrim Yılmaz; Özcan Bör (SpringerOpen, 2023)
Abstract Background In childhood acute lymphocytic leukemia (ALL), relapse is most commonly seen in the bone marrow (10-20%), followed by the central nervous system (3-8%). Isolated skin relapse is very rare in ALL. We report an 8-year-old child presented with isolated skin relapse. Case presentation An eight-year-old female patient presented with swelling on the scalp 3 months after the completion of the ALLIC-BFM 2009 chemotherapy protocol administered due to the diagnosis of precursor B-cell (pre-B) ALL. Physical examination revealed a hard, painless, hyperemic, nodule-shaped lesion measuring 2 × 1 cm on the right parietal bone. Atypical hematopoietic cells with the prominent nucleolus, narrow cytoplasm, and immunohistochemically stained with CD 10, 19, 22, 79-a, and TdT were observed in the histopathological examination of the skin lesion. There was no blast in the bone marrow aspiration smear and cerebrospinal fluid. The patient was diagnosed with aleukemic leukemia cutis (LC) and pre-B ALL, presenting as an isolated relapse. Conclusion Aleukemic LC is a very rare finding after leukemia treatment. It may present with various cutaneous lesions, such as a papule, macule, plaque, nodule, palpable purpura, and ulcerative lesions. Leukemia cutis should be considered in the differential diagnosis of skin lesions developing during or after treatment in children with leukemia.